Estrategias de atención al cliente y su incidencia en las ventas de la empresa ferromax del ecuador s.a. del cantón Quevedo, 2022. - Taipe Calo, Jonathan Agustín (2024)
In the company Ferromax Del Ecuador S.A. dedicated to the production and commercialization of construction materials, a research was carried out with the general objective of evaluating the impact of the customer service strategies implemented by FERROMAX DEL DECUADOR S.A. of the Quevedo Canton, and how they affect their sales and competitiveness within the local hardware sector. In order to carry it out, we used a methodology that combined descriptive and documentary research, together with scientific, deductive and analytical methods. In terms of resources, direct observation by means of a technical sheet and surveys of employees and frequent customers of the hardware store were used. The results revealed that while there are several areas where the staff meets basic customer service expectations, there are significant opportunities for improvement in terms of operational efficiency and sales techniques, so the recommendation is to implement formal protocols for greeting and handling complaints, diversify customer service strategies, and provide training and education to staff to improve the customer experience and increase sales.